Pengaruh Mikroba Dalam Pembuatan Keju Dengan Fermentasi Asam Laktat - Siti Aisyah; Teky Hayuningtyas; Wiwin Wiwin; Eka Fitrian Ramadhani; Liss Dyah Dewi A (STIKes Ibnu Sina Ajibarang, 2024)
Cheese is a food fermented by lactic acid bacteria and fungi. Cheese has many important nutrients and is high in energy. The type of milk used (species, lactation stage, full fat, low fat, or skim), the manufacturing process, and, to a lesser extent, the air-insoluble nutritional quality of the milk (coagulated casein, In cheese curds, colloidal minerals, fat, and fat-soluble vitamins remain, while the air-soluble components of milk are whey protein, lactose, vitamins, and air-soluble minerals. But the loss of air-soluble B vitamins can be compensated by microbial synthesis during cooking to a certain extent .The biological proteins of cheese are very beneficial.The protein content of cheese ranges from 4 to 40%, depending on the variety, and is usually higher than the fat.Therefore, before consumption, cheese proteins break down in large quantities, and this has an impact on the proteolytic function of the intestine. The coagulation process takes fifteen to thirty minutes. The milk will coagulate into curd and then be reheated at a temperature of 38 degrees Celsius.